2012
DOI: 10.7314/apjcp.2012.13.5.2341
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Evaluation of Breast Cancer in Ecological areas of Kazakhstan - Association with Pollution Emissions

Abstract: The aim of the research was to evaluate the incidence of breast cancer in the ecological areas of Kazakhstan and assess the potential . A retrospective study of 11 years (1999 to 2009) was conducted using descriptive and analytical methods. The incidence of breast cancer was the lowest in the Aral-Syr Darya area (18.6±0.80/100,000), and highest in the Irtysh area (48.9±1.90/100,000), with an increasing trends over time in almost all areas. A direct strong correlation between the degree of contamination with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…and null genotypes of both GSTM1 and GSTT1 genes may confer elevated risk of chronic myeloid leukaemia (Bhat et al, 2012), implying carcinogen involvement. It is of clear intest that earlier studies of breast cancer showed highest incidences where pollution was highest, including Pavlodar (Bilyalova et al, 2012). Similarly laryngeal cancer demonstrates highest incidences in North Kazakhstan and Pavlodar (Igissinov 2013a), like leukemia here.…”
Section: Discussionmentioning
confidence: 56%
“…and null genotypes of both GSTM1 and GSTT1 genes may confer elevated risk of chronic myeloid leukaemia (Bhat et al, 2012), implying carcinogen involvement. It is of clear intest that earlier studies of breast cancer showed highest incidences where pollution was highest, including Pavlodar (Bilyalova et al, 2012). Similarly laryngeal cancer demonstrates highest incidences in North Kazakhstan and Pavlodar (Igissinov 2013a), like leukemia here.…”
Section: Discussionmentioning
confidence: 56%
“…Whether there might be any correlate between rates of cancer positives and screenees by geographical location in Kazakhstan should also be assessed, taking into consideration the findings of Bilyalova et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Reported risk factors include unfavorable living conditions, chronic stress, unilateral breastfeeding, breastfeeding less than 3 months and over 2 years, abortions, and hereditary predisposition (Toleutay et al, 2013). In addition, a direct strong correlation between the degree of contamination with high pollution emissions in the atmosphere from stationary sources and the incidence of breast cancer has been described (Bilyalova et al, 2012). The situation in Central Asia may be complicated by higher rates in Russians than Turkic inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…According to the last publications, trends in incidence of major forms of cancer were studied in Aral-Syr Darya ecological area of Kazakhstan and high growth rates of BC were revealed (Igissinov et al, 2011), also the correlation of BC with air pollution was found (Bilyalova et al, 2012). There were no studies on risk factors of BC in Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%